Anteriolateral versus anterior–posterior electrodes in external cardioversion of atrial fibrillation: A systematic review and meta‐analysis of clinical trials - Karam R. Motawea (13954362) (2023)
The efficacy of anteriolateral versus anterior–posterior electrode positions in the success of atrial fibrillation's (AF) electrical cardioversion is unclear. Our aim is to perform a meta‐analysis to compare the success rate of both electrode positions. PUBMED, WOS, OVID, and SCOPUS were searched. Inclusion criteria were clinical trials that compared anterior–lateral with anterior–posterior electrodes in external cardioversion of AF. After the full‐text screening, 11 trials were included in the analysis. The total number of patients included in the study is 1845. The pooled analysis showed a statistically significant association between anterior–lateral electrode and increased cardioversion rate of AF (odds ratio [OR] = 1.40, 95% confidence interval [CI] = 1.02–1.92, p = .04). Subgroup analysis revealed a statistically significant association between the anterior–lateral electrode and increased cardioversion rate of AF in subgroups of less than five shocks, patients with 60 years old or more and patients with left atrial (LA) diameter >45 mm (OR = 1.72, 95% CI = 1.17–2.54, p = .006), (OR = 1.73, 95% CI = 1.18–2.54, p = .005), and (OR = 1.86, 95% CI = 1.04–3.34, p = .04), respectively. Anteriolateral electrode is more effective than anterior–posterior electrode in external cardioversion of AF, particularly in patients who have received less than 5 shocks, are 60 years old or older and have a LA diameter greater than 45 mm. Other Information Published in: Clinical Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/clc.23987